Correction: Social and juristic challenges of artificial intelligence - Perc, Matjaž; Ozer, Mahmut; Hojnik, Janja (Springer Science and Business Media LLC, 2019)
An amendment to this paper has been published and can be accessed via a link at the top of the paper